2020
DOI: 10.1186/s13287-020-01608-8
|View full text |Cite|
|
Sign up to set email alerts
|

Protective effects of human iPS-derived retinal pigmented epithelial cells on retinal degenerative disease

Abstract: Background Retinitis pigmentosa (RP) is an inherited retinal disease characterized by progressive loss of photoreceptor cells. This study aim at exploring the effect of retinal pigment epithelium (RPE) derived from human-induced pluripotent stem cell (hiPSC-RPE) on the retina of retinal degeneration 10 (rd10) mice, which are characterized with progressive photoreceptor death. Methods We generated RPE from hiPSCs by sequential supplementation with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 43 publications
4
23
1
1
Order By: Relevance
“…Morphological evaluation also suggested that the transplanted RSCs were integrated into the host retina, implying its potential to substitute for the damaged cells. This observation was consistent with the previous reports [ 35 , 36 ]. The preliminary data from ERG further demonstrated the potential repair ability of RSCs, which was restricted in the outer layer of the damaged retina.…”
Section: Discussionsupporting
confidence: 94%
“…Morphological evaluation also suggested that the transplanted RSCs were integrated into the host retina, implying its potential to substitute for the damaged cells. This observation was consistent with the previous reports [ 35 , 36 ]. The preliminary data from ERG further demonstrated the potential repair ability of RSCs, which was restricted in the outer layer of the damaged retina.…”
Section: Discussionsupporting
confidence: 94%
“…Morphological evaluation also suggests that the transplanted RSCs were integrated into the host retina, implying its potential to substitute for the damaged cells. This observation is consistent with previous reports [36,37]. However, differentiation of the transplanted RSCs was not distinguishable through light microscopy.…”
Section: Discussionsupporting
confidence: 93%
“…Morphological evaluation also suggested that the transplanted RSCs were integrated into the host retina, implying its potential to substitute for the damaged cells. This observation was consistent with the previous reports [35,36]. The preliminary data from ERG further demonstrated the potential repair ability of RSCs, which was restricted in the outer layer of the damaged retina.…”
Section: Discussionsupporting
confidence: 93%